MODELING THE RELATIONSHIP BETWEEN NET ATOMIC CHARGE AND THE ACTIVITY OF 4-HYDRAZINYL-6-PHENYLPYRIMIDINE-5 CARBONITRILE DERIVATIVES AS ANTI-BREAST CANCER AGENTS - Putri, Fitria Eka; Azra, Fajriah (Walisongo Journal of Chemistry, 2025)
A quantitative structure-activity relationship (QSAR) analysis was conducted on 15 derivatives of 4-hydrazinyl-6-phenylpyrimidine-5-carbonitrile to investigate the relationship between atomic charge and anti-breast cancer activity (MCF-7 cell line) based on experimental log IC₅₀ values. Descriptor data were obtained through AM1 semi-empirical quantum mechanical calculations using HyperChem. A multiple linear regression model with the backward elimination method was employed to establish the quantitative relationship between net atomic charge and log IC₅₀, yielding the following QSAR model: log IC₅₀ = -415.573 − 224.759(qC2) + 175.860(qC5) + 1307.672(qC6) + 1251.123(qC8) + 1142.590(qC9) − 3606.800(qC10) + 3.840(qC13); with n = 15, R = 0.899, R² = 0.808, Fₒ/Fₜ = 1.002, and PRESS = 0.043. The results indicate a statistically significant correlation between atomic charge and biological activity.